Effects of straw return and straw biochar on soil properties and crop growth: A review - Chen, Limei; Sun, Songlin; Yao, Bin; Peng, Yutao; Gao, Chongfeng; Qin, Tian; Zhou, Yaoyu; Sun, Chaoran; Quan, Wei (Frontiers in Plant Science, 2022)
Straw return is an effective method for disposing agricultural residues. It not only utilizes agricultural waste but also improves soil. In the current review, different crop straw and its characteristics were highlighted, and patterns of straw return were explored (including straw return, straw biochar return, and their combined with fertilizer return), as well as their environmental impacts were outlined. In addition, the effects of straw return and straw biochar amendment on soil properties [e.g., pH, soil organic carbon (SOC), soil nitrogen (N)/phosphorus (P)/potassium (K), soil enzyme activities, and soil microbes] were discussed. Information collected from this review proposed that straw return and straw biochar return or in combination with fertilizer is an applicable way for improving soil fertility and enhancing crop production. Straw return is beneficial to soil physicochemical properties and soil microbial features. The rice straw has positive impacts on crop growth. However, there are different climate types, soil types and crops in China, meaning that the future research need long-term experiment to assess the complex interactions among straw, soil, and plant eco-systems. Accordingly, this review aims to provide available information on the application of straw return in terms of different patterns of its to justify and to expand their effective promotion.